2014
DOI: 10.1007/s00784-014-1216-3
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD40 ligand: a novel biomarker in the pathogenesis of periodontal disease

Abstract: Positive association of its local levels with those in serum further implicates the possibility of widespread systemic effects of this infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
1
11
0
1
Order By: Relevance
“…This molecule is also essential for T‐helper cell activation, is a well‐known risk indicator of cardiovascular diseases and GCF levels of sCD40L can be elevated in periodontitis (Chaturvedi et al. ). Platelet‐derived growth factor BB is better known for its use in periodontal regeneration (Reynolds et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This molecule is also essential for T‐helper cell activation, is a well‐known risk indicator of cardiovascular diseases and GCF levels of sCD40L can be elevated in periodontitis (Chaturvedi et al. ). Platelet‐derived growth factor BB is better known for its use in periodontal regeneration (Reynolds et al.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble human CD40 ligand is a member of the TNF superfamily and it binds to CD40 on the surface of antigen-presenting cells and can activate B cell maturation (Hostager & Bishop 2013). This molecule is also essential for T-helper cell activation, is a well-known risk indicator of cardiovascular diseases and GCF levels of sCD40L can be elevated in periodontitis (Chaturvedi et al 2015). Platelet-derived growth factor BB is better known for its use in periodontal regeneration (Reynolds et al 2015), but its presence in GCF has been associated with phenytoininduced gingival enlargement (Kuru et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Platelets are the major source of sCD40L in the circulation [ 65 , 97 , 98 ]. The normal range of sCD40L in the serum of a healthy adult is estimated at 0.79 to 4.7 ng/mL, by means of immunoassay techniques [ 99 , 100 , 101 ].…”
Section: Platelet Cd40lmentioning
confidence: 99%
“…Accidents were attributed to other causes, which were sometimes reported as unidentified. Soluble CD40L gained attention when progress was made in the field of hemostasis and thrombosis, which outlined the role of platelets and leukocytes in the formation of atheroma plaque deposition and led to the proposal that cardiovascular disease is inflammatory [ 16 , 99 , 138 , 139 , 140 , 141 , 142 , 143 ].…”
Section: Cd40l and Platelet Component Transfusionmentioning
confidence: 99%
“…21 Contrary to our result on the negative correlation between periodontitis severity and sCD40L salivary levels, a recent case-control study reported a positive correlation between this marker in GCF and periodontitis severity. 22 To our knowledge, there are no published studies on the correlation of periodontal severity and the expression of the other two biomarkers tested (i.e. Granzyme B and AFP).…”
Section: Discussionmentioning
confidence: 96%